Penerapan ilmu tasawuf dalam berekonomi - Farika, Alya (Maliki Interdisciplinary Journal, 2024)
The emergence of Sufism coincided with the birth of the Islamic religion, namely since Muhammad SAW was sent as the Messenger of Allah to all mankind and the entire universe. He implemented tawanuts and seclusion in the Hira Cave to escape the desires of the world. The main and main element in Sufism is to purify oneself and the ultimate goal is eternal happiness and salvation. But basiclly Sufism is the implementation of ihsan which means worshiping Allah as if seeing Him. If you cannot do that, then you must realize that Allah sees you, which is the reality of someone’s appreciation of their religion. In everyday life we ​​should apply the knowledge of Sufism, especially in carrying out economic activities where we seek provisions for the world and it would be good if balanced with provisions for the afterlife.